Training as a key to labor integration of foreigners. Improvements and pending issues of RD 1155/2024 - Torró i Calabuig, Aitana (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The new migration law, enacted through Royal Decree 1155/2024 of November 19, places the training of foreigners at the core of its framework as a pathway to administrative regularization and as a means of entry and residence in the territory. Two key mechanisms will be analyzed in this context: socio-educational rooting and long-term stay permits for study purposes. These mechanisms highlight the increasing importance of education in granting foreign individuals an optimal rights-based status for legal integration. In this way, it will be shown how an inclusive and protective approach to the right to education may serve as a counterbalance to the restrictive approach to the right to work for foreign individuals. Finally, the potential shortcomings and ongoing challenges in the new immigration regulation will be adressed, with particular emphasis on the recognition of qualifications and the regulation of labor-related migration and its integration.
Keywords: Labor integration; training; education; immigration; RD 1155/2024; regularization; labor migration; social rights; equality